Moving beyond 'rates, roads and rubbish': How do local governments make choices about healthy public policy to prevent obesity? - Allender, S; Gleeson, E; Crammond, B; Sacks, G; Lawrence, M; Peeters, A; Loff, B; Swinburn, B (2009)
While the causes of obesity are well known traditional education and treatment strategies do not appear to be making an impact. One solution as part of a broader complimentary set of strategies may be regulatory intervention at local government level to create environments for healthy nutrition and increased physical activity. Semi structured interviews were conducted with representatives of local government in Australia. Factors most likely to facilitate policy change were those supported by external funding, developed from an evidence base and sensitive to community and market forces. Barriers to change included a perceived or real lack of power to make change and the complexity of the legislative framework. The development of a systematic evidence base to provide clear feedback on the size and scope of the obesity epidemic at a local level, coupled with cost benefit analysis for any potential regulatory intervention, are crucial to developing a regulatory environment which creates the physical and social environment required to prevent obesity. © 2009 Allender et al; licensee BioMed Central Ltd.